The Effects of Home–School Dissonance on Individual and School Outcomes for Māori and European New Zealand Adolescents - Jose, Paul E.; Rata, Arama; Richards, Alex (Frontiers in Education, 2017)
Researchers have speculated that children and adolescents who experience an incongruity between the cultures of home and school (termed “home-school dissonance” or HSD) perform more poorly in the school setting and evidence poorer adjustment in general. A sample of 476 Māori and 1,024 European New Zealand (ENZ) adolescents, aged 11-16 years at Time 1, completed self-report measures of home-school dissonance, family connectedness, school connectedness, aspirations, positive relations with teacher, self-reported schoolwork quality, and other related measures three times separated by one year each. As predicted, Māori youth reported higher levels of HSD compared to ENZ youth. In addition, latent growth curve modelling showed that an increase in home-school dissonance over three years positively predicted negative outcomes and negatively predicted positive outcomes. We concluded that Māori youth experience a disconnection between the contexts of home and school, and this dissonance is associated with a range of poor psychological and educational outcomes.